Application of a Blended Learning Model in Agricultural Vocational High Schools - Sari Nurmayani; Yatti Sugiarti; Siti Mujdalipah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
Based on case studies that have been conducted in SMK Pertanian Pembangunan Negeri Lembang, waste treatment subjects still used a conventional method, and the students were less enthusiastic in the learning process. Therefore, the implementation of more interactive learning models such as blended learning with Edmodo is one of alternative models to resolve the issue thus the purpose of this study is to formulate the appropriate learning syntax for the implementation of blended learning with Edmodo to agree the requirement characteristics of students and waste treatment subject and explain the learning outcome obtained by students in the cognitive, affective and psychometric aspects on the subjects of waste treatment. This study was conducted by the method of classroom action research (CAR) with a Mc. Tagart model. The results of this study concluded that the implementation of blended learning with Edmodo on the subjects of waste treatment can improve the students’ learning outcomes in the cognitive, affective and psychometric aspects with the maximum increase in the value of N-gain 0.82, as well as students’ learning completeness criteria reached 100% in cycle 2. The formulation of the appropriate learning syntax for the blended learning model implementation with Edmodo in the waste treatment subject are (1) Self-paced learning, (2) Group networking, (3) Live Event-collaboration, (4) Association- communication, (5) Assessment-Performance material supports